Efficient edge coupler for higher order mode fiber-to-chip coupling - Lai, Yaxiao (2017)
An edge coupler composed of two tapered waveguides and a Y-branch for LP11-TE1 mode coupling and mapping is proposed on silicon-on-insulator platform. An average 3 dB coupling loss can be acquired within 100 nm bandwidth.